Therapeutic effect of demethylated hydroxylated phillygenin derivative on Helicobacter pylori infection - Li, Ru-Jia; Xu, Jia-yin; Wang, Xue; Liao, Li-juan; Wei, Xian; Xie, Ping; Xu, Wen-yan; Xu, Zhen-yi; Xie, Shuo-hua; Jiang, Yu-ying; Huang, Liang; Wang, Lu-yao; et al. (Frontiers in Microbiology, 2023)
Modifying and transforming natural antibacterial products is a novel idea for developing new antibiotics. Phillygenin has an inhibitory effect on H. pylori. The aim of the present study was to prepare a phillygenin derivative (PHI-Der) through demethylation and hydroxylation. The minimum inhibitory concentration of 18 strains of H. pylori from different sources was 8-32 μg/mL in vitro, and the activity increased 2-8 times than that of phillygenin. PHI-Der could significantly inhibit the colonization of H. pylori in vivo, reduce the inflammatory response, and promote the repair of inflammatory damage. Further, we used SwissTargetPrediction to predict that its main targets are ALOX5, MCL1, and SLC6A4, and find that it can inhibit bacterial biofilm formation and reduce bacterial infection of cells. It can enhance the intracellular oxidative capacity of H. pylori to inhibit H. pylori growth. Further, it could prevent the oxidation of H. pylori-infected cells and reduce the inflammatory response, which plays a role in protection. In conclusion, compared to phillygenin, PHI-Der had better antibacterial activity and was more effective in treating H. pylori infection. It has characteristics of high safety, specificity, resistance to drug resistance and better antibacterial activity than phillygenin，it’s a good antioxidant for host cells.